Relationship between volatile compounds and consumer-based sensory characteristics of bacon smoked with different Brazilian woods - Saldaña E. (2019)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project No. 2016/15012-2. Erick Saldaña received the support of the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC” from Peru, in the framework of the CIENCIACTIVA programme, through the award of a PhD scholarship under contract agreement No. 104-2016-FONDECYT.